Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Ellie_751

  • 3 years ago

How do you put, (y-2)/3=x into the form of y=mx+c???

  • This Question is Closed
  1. archey456
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    multiply both side of the equation by 3 giving y-2 = 3x next add 2 to both sides giving y = 3x + 2

  2. marissa777
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Y=x/3-2

  3. Ellie_751
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Thankyou :)

  4. tasreeb
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Y-2/3=X Y-2=3X Y=3X+2, m=3nd c=2

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy